Respuesta :

Answer: 8^10

Add up the exponents 6 and 4 to get 6+4 = 10. This is using the rule a^b*a^c = a^(b+c). In this case, a = 8, b = 6, c = 4.

When you multiply,  the exponents are added. For example 3² × [tex]3^{7}[/tex] = [tex]3^{9}[/tex]

When you divide, the exponents are subtracted. For example [tex]4^{5}[/tex] ÷ [tex]4^{2}[/tex] = [tex]4^{3}[/tex]

This only works when the Base numbers are same: For example, you can't do this with [tex]5^{6}[/tex] ×[tex]9^{6}[/tex] , because the base of one is 5, and the other is 9.  For it to work they would have to be the same.

Answer:

So for your question the answer would be:  [tex]8^{6}[/tex] × [tex]8^{4}[/tex] = [tex]8^{10}[/tex]  ( [tex]^{6}[/tex] + [tex]^{4}[/tex] = [tex]^{10}[/tex] )